The Brazilian Case: Towards a Paradigm of Trans‑Colonial Studies - Ewa Łukaszyk (Ksiegarnia Akademicka Publishing, 2021)
The aim of this article is to discuss the limited applicability of the “standard” post‑colonial method in the analysis of the Brazilian literature and culture. A new, trans‑colonial paradigm is proposed instead, focusing on emerging idiosyncrasies rather than on the process of critical deconstruction of the European discourses and ideologies. In a comparative perspective confronting the studied case with other situations in the world, the article presents particular circumstances that shaped the trans‑colonial pattern of development of the Brazilian culture. The factors and phenomena taken into the account are: the proportions of economic and cultural strength between the colony and its metropolis, the dynamics of the identity search that followed the moment of formal independence, the peculiarity related to the predominance of a non‑printed (oral or handwritten) culture and finally the emergence of cultural distinctiveness alien to Eurocentric canons.